Physical Activities That Influence Pregnant Women’s Well-Being: Literature Review - Ermiati, Ermiati; Mamuroh, Lilis; Srimurni, Nita Ayu (Journal of Nursing Care, 2025)
Pregnancy and childbirth are physiological processes that influence maternal mortality and morbidity risk factors. Proper mental and physical preparation is essential to prevent pathological conditions that may affect pregnant women. One effective intervention is engaging in physical activity, which positively impacts both the mother and fetus. This literature review aims to examine the relationship between physical activity and the health of pregnant women in physical, psychological, socio-economic, cultural, and environmental aspects. This study employs a literature review methodology using the PRISMA (Preferred Reporting Items for Systematic Reviews and MetaAnalyses) approach. Article selection was conducted using the PICO (Population, Intervention, Comparison, Outcome) framework, with keywords such as “pregnant women,” “physical activity,” “sports,” “benefits,” and “exercise” in Indonesian and English. The literature search was performed using Sage Journals, Scopus, and Google Scholar for articles published between 2019 and 2024 also free full-text. A total of six relevant studies were selected based on inclusion and exclusion criteria. The findings indicate that physical activity offers significant benefits for pregnant women and fetuses, particularly in improving their quality of life both physically and mentally. Pregnant women in rural areas tend to be more physically active than those in urban areas, and light exercises such as walking or yoga help reduce the body’s burden, enhance sleep quality, alleviate stress, and prevent pregnancy complications. Further longitudinal research and education are necessary to understand the long-term effects of physical activity on pregnant women and to raise awareness of its benefits, especially in urban areas.Keywords: Maternal well-being, Pregnancy, Physical activity